2019
DOI: 10.1001/jama.2019.19365
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes by Race and Ethnicity in the United States, 2011-2016

Abstract: The prevalence of diabetes among Hispanic and Asian American subpopulations in the United States is unknown. OBJECTIVE To estimate racial/ethnic differences in the prevalence of diabetes among US adults 20 years or older by major race/ethnicity groups and selected Hispanic and non-Hispanic Asian subpopulations. DESIGN, SETTING, AND PARTICIPANTS National Health and Nutrition Examination Surveys, 2011-2016, cross-sectional samples representing the noninstitutionalized, civilian, US population. The sample include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
311
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(333 citation statements)
references
References 22 publications
18
311
2
2
Order By: Relevance
“…In their report [14], men have higher incidence than women in all age groups, which is similar to our results. Sex and gender differences in genetics, pathophysiology, immune system, myocardial in ammation, and cardiac remodeling [19], together with different prevalence rate of diabetes in various race and ethnicities [20], might have been responsible for such discrepancy in the results of the previous study and ours. Androgens promote cardiac hypertrophy, and men develop atherosclerotic plaques earlier and more extensively than women; estrogen in women prevents apoptosis in cardiac myocytes, inhibits reactive oxygen species-induced cardiac damage, and opposes mechanisms that lead to cardiac hypertrophy and brosis [19].…”
Section: Discussioncontrasting
confidence: 77%
“…In their report [14], men have higher incidence than women in all age groups, which is similar to our results. Sex and gender differences in genetics, pathophysiology, immune system, myocardial in ammation, and cardiac remodeling [19], together with different prevalence rate of diabetes in various race and ethnicities [20], might have been responsible for such discrepancy in the results of the previous study and ours. Androgens promote cardiac hypertrophy, and men develop atherosclerotic plaques earlier and more extensively than women; estrogen in women prevents apoptosis in cardiac myocytes, inhibits reactive oxygen species-induced cardiac damage, and opposes mechanisms that lead to cardiac hypertrophy and brosis [19].…”
Section: Discussioncontrasting
confidence: 77%
“…7 The intake of cheap foods with low nutrient, high energy (eg, refined grains and trans fats or saturated fats) is a major risk factor for progression of T2D. 8 Compared with non-Hispanic whites, rates of T2D are higher among US Hispanic/Latino adults, 9 and this population is also more likely to participate in federal programmes such as the Supplemental Nutrition Assistance Program (SNAP). 10 A recent microsimulation study suggested that implementing healthy food prescriptions within government healthcare programmes could generate substantial health gains and be highly costeffective.…”
Section: Introductionmentioning
confidence: 99%
“…More than 9/10 people with diabetes have type 2 diabetes. An estimated one-third of the adult US population (approximately 84 million) is at risk for type 2 diabetes (ie, have prediabetes), based on having a fasting glucose (FG) or hemoglobin A1c (HbA1c) level above the normal range but below the threshold for diabetes ( 2 , 3 ). People with prediabetes progress to diabetes at a rate of about 5% to 10% per year ( 4 ).…”
mentioning
confidence: 99%